Remifentanil versus Propofol/Fentanyl Combination in Procedural Sedation for Dislocated Shoulder Reduction; a Clinical Trial - Monsef Kasmaee, Vahid; Zia Zibari, Seyed Mahdi; Aghajani Nargesi, Marjan (Archives of Academic Emergency Medicine, 2019)
Introduction: Procedural sedation and analgesia (PSA) is a fundamental skill for every emergency physician. This study aimed to compare the PSA characteristics of remifentanil with propofol/fentanyl combination. Methods: In this double-blind randomized clinical trial, the procedural characteristics and number of failures, as well as adverse events were compared between groups treated with either remifentanil or propofol/fentanyl combination consisting of 15-60 year old patients referring to emergency department following acute anterior shoulder dislocation. Results: 64 patients were randomly assigned to either remifentanil (32 cases) or propofol/fentanyl, (32 cases) groups. The two groups were similar regarding mean age, sex, and pain severity at the time of presentation to ED. The two regimens had the same efficiency regarding pain management (100% success rate). 22 (68.8%) cases in remifentanil group and 4 (12.5%) cases in propofol/fentanyl group had failed in muscle relaxation (p < 0.001). In the group receiving remifentanil, onset of action (p = 0.043) and recovery time (p < 0.001) were significantly shorter. 10 (31.3%) cases in remifentanil group and 11 (34.4%) cases in the other group experienced adverse events (p =0.790). There was a significant difference between groups regarding the type of adverse events (p = 0.003). Conclusion: Compared to propofol/fentanyl combination, remifentanil has equal efficiency in pain management, lower success rate in muscle relaxation, significantly higher frequency of apnea, and shorter onset of action and recovery times in PSA for reduction of anterior shoulder dislocation.